Feature Selection Approach to Detect DDoS Attack Using Machine Learning Algorithms - Azmi, Muhammad Aqil Haqeemi; Foozy, Cik Feresa Mohd; Sukri, Khairul Amin Mohamad; Abdullah, Nurul Azma; Hamid, Isredza Rahmi A.; Amnur, Hidra (Society of Visual Informatics, 2021)
Distributed Denial of Service (DDoS) attacks are dangerous attacks that can cause disruption to server, system or application layer. It will flood the target server with the amount of Internet traffic that the server could not afford at one time. Therefore, it is possible that the server will not work if it is affected by this DDoS attack. Due to this attack, the network security environment becomes insecure with the possibility of this attack. In recent years, the cases related to DDoS attacks have increased. Although previously there has been a lot of research on DDoS attacks, cases of DDoS attacks still exist. Therefore, the research on feature selection approach has been done in effort to detect the DDoS attacks by using machine learning techniques. In this paper, to detect DDoS attacks, features have been selected from the UNSW-NB 15 dataset by using Information Gain and Data Reduction method. To classify the selected features, ANN, NaÃ¯ve Bayes, and Decision Table algorithms were used to test the dataset. To evaluate the result of the experiment, the parameters of Accuracy, Precision, True Positive and False Positive evaluated the results and classed the data into attacks and normal class. Hence, the good features have been obtained based on the experiments. To ensure the selected features are good or not, the results of classification have been compared with the past research that used the same UNSW-NB 15 dataset. To conclude, the accuracy of ANN, NaÃ¯ve Bayes and Decision Table classifiers has been increased by using this feature selection approach compared to the past research.